2020
DOI: 10.1111/liv.14464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osteopontin on the development of non‐alcoholic liver disease and related hepatocellular carcinoma

Abstract: Background & aims Osteopontin, a multifunctional protein and inflammatory cytokine, is overexpressed in adipose tissue and liver in obesity and contributes to the induction of adipose tissue inflammation and non‐alcoholic fatty liver (NAFL). Studies performed in both mice and humans also point to a potential role for OPN in malignant transformation and tumour growth. To fully understand the role of OPN on the development of NAFL‐derived hepatocellular carcinoma (HCC), we applied a non‐alcoholic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Studies by AlexanderD.Nardo et al. have indicated that the imbalance of SPP1 expression can promote the malignant development of hepatocellular carcinoma ( 29 ). LiguangYang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by AlexanderD.Nardo et al. have indicated that the imbalance of SPP1 expression can promote the malignant development of hepatocellular carcinoma ( 29 ). LiguangYang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted phosphoprotein 1 (SPP1) also called as Osteopontin (OPN), it has been reported to be involved in tumor progression, metastasis and suggested as a promising prognosis/therapeutic target biomarker (28). Studies by AlexanderD.Nardo et al have indicated that the imbalance of SPP1 expression can promote the malignant development of hepatocellular carcinoma (29). LiguangYang et al found that the overexpression of SPP1 was associated with poor survival and could promote the proliferation of HCC cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Using a model of HCC with a modified choline–deficient diet, Opn −/− mice show less tumors, ( 60 ) but streptozotocin‐injected Opn −/− mice on an HFD show the reverse. ( 35 ) These discrepancies may be explained by the cellular origin of OPN in these models or by the effect of i‐OPN compared to s‐OPN. Ongoing studies from our laboratory are exploring these possibilities.…”
Section: Opn and Hccmentioning
confidence: 94%
“…( 34 ) However, streptozotocin‐injected diabetic Opn −/− mice on an HFD show increased liver triglycerides. ( 35 ) Moreover, Opn −/− mice fed the methionine choline–deficient diet or an HFD with 2% cholesterol show no effect on liver steatosis, but protection from fibrosis. ( 36 ) OPN plays a role in the progression of nonalcoholic steatohepatitis (NASH) by inhibiting autophagy ( 37 ) and increasing hepatocyte senescence.…”
Section: Opn and Hepatic Steatosismentioning
confidence: 99%
“…SPP1 deficiency may reduce liver-related mortality, which may be associated with the promotion of a systemic pro-inflammatory milieu by SPP1 . This suggests that SPP1 plays a dual role in the pathogenesis of fatty liver and that SPP1 may be involved in the internal control of excessive lipid uptake in the liver, thereby protecting the liver from lipotoxicity, apoptosis, and subsequent fibrosis and hepatocyte proliferation ( 26 ).…”
Section: Discussionmentioning
confidence: 99%